Centralizing the cut: a feminist, queer, crip response to powerful playgrounds. (December 2022) - van Saarloos, Simon(e)
Responding to Erik Rietveld's inaugural lecture, this commentary asks which bodies and what sites of design and architecture are centralized when thinking about "The Affordances of Art for Making Technologies"? Departing from personal experience and Nicholas Mirzoeff's counterhistory of visuality, I analyze what it means to imagine "the end of sitting." Through an engagement with crip theory and disability activism, I aim to understand which architectural sites should be disrupted. RAAAF's practice of cutting and splitting closely relates to the work of the '70s artist Gordon Matta-Clark. But the radical proposals of both RAAAF and Matta-Clark engage with power in almost oppositional ways. While Matta-Clark offers the cut as a final space, RAAAF aims to create new worlds. I question the need for new worlds, since they are built on current power structures, instead of dismantling them.